Compatibility of Some Commercial Meat Products with the Egyptian Standards Regarding Chemical Additives - El Bayoumi, Zakaria H.; Edris, Abobakr M.; Latif, Hossam M.; Shawish, Reyad R. (Journal of Advanced Veterinary Research, 2023)
Chemical additives were found to be the most widely used and least expensive flavouring and preservatives for meat products, but they must be used within safe-permissible levels to protect customers from any negative effects. With reference to the most recent updates of the Egyptian standards, this study examines the levels of nitrite, phosphate, ascorbic acid, and monosodium glutamate as examples of chemical additives in one hundred and sixty random samples of raw minced meat, beef burgers, sausages, and frankfurters (40 of each), which were collected from different supermarkets located in Shibin Elkom city, Menoufia governorate, Egypt. While nitrite was not found in the minced meat samples, out of the analyzed samples, 92.5%, 97.5, and 100% of the tested sausage, burger, and frankfurter samples, respectively, were within the permitted limits (PL) (≤ 100 ppm) regarding their nitrite level. Furthermore, when it came to ascorbic acid PL (≤ 500 ppm), 72.5%, 100%, 87.5%, and 100% of the minced beef, sausage, burger, and frankfurter samples were within PL, respectively. Additionally, 100%, 90%, 95.0%, and 97.5% of the analyzed minced beef, sausage, burger, and frankfurter samples fell below the acceptable range for monosodium glutamate level (≤ 5000 ppm), respectively. Furthermore, the tested minced beef and sausage samples had no phosphate, whereas 72.5% of the investigated frankfurter samples were within the PL, and all of the studied burger samples were outside the PL (≤ 0.3%). So, it is advised to continuously monitor the meat production market and carefully enforce the safety requirements.